P771 Clinical trial of cefixime for the treatment of early syphilis – preliminary results. (14th July 2019) - Stafylis, Chrysovalantis; Tellalian, David; Raich, Aishwarya; Dong, Huan; Burian, Pamela; Okada, Cliff; Millner, Carl; Carroll, James; Mejia, Cristopher; Joseph, Arberletia; Klausner, Jeffrey
Abstract : Background: Increasing incidence of syphilis in the United States and penicillin shortages internationally call for research on alternative treatment options. In this randomized, multisite, open-label, non-comparative clinical trial, we are evaluating the efficacy of cefixime as treatment of early syphilis. Methods: Eligible participants are 18 years or older, have laboratory confirmed early syphilis (new Rapid Plasma Reagin [RPR] titer ≥1:8 or 4-fold titer rise in past 12 months), and no concomitant antibiotic use. Patients with HIV infection must have undetectable viral load in the past 12 months and CD4+ count ≥350 cells/μl. Participants were randomized to receive either 2.4M IU benzathine penicillin G intramuscularly once or cefixime 400 mg orally twice a day, for ten days. Participants return for follow-up at 3, 6, and 12 months post-treatment for laboratory testing. The main outcome is a 4-fold RPR titer decrease at 6 months post-treatment. Results: To date, 27 participants (15 penicillin, 12 cefixime) are enrolled. The majority of the study population is men (26/27), Latino (15/27), and HIV-infected (25/27). Eight participants completed their 3-month follow up (4 cefixime/4 penicillin). In the cefixime arm, 3/4 participants had an equal or greater than four-fold decrease in the RPR titer, and 1/4 had a two-fold decrease. In the penicillin arm, 2/4 participants had an equal or greater than 4-fold decrease in the RPR titer, 1/4 had a two-fold decrease, and 1/4 is missing data. Conclusion: Enrollment is still open and data collection ongoing. Initial results are encouraging. Disclosure: No significant relationships.